A Novel Technique for Detecting Instability of the Distal Radioulnar Joint in Complete Triangular Fibrocartilage Complex Lesions - Hess, Florian; Farshad, Mazda; Sutter, Reto; Nagy, Ladislav; Schweizer, Andreas (Journal of Wrist Surgery, 2012)
We performed this study to investigate whether discrepancy of bilateral dorsovolar shift of the distal radioulnar joint (DRUJ) is decisive for the diagnosis of DRUJ instability. Although several cadaver studies have quantified the amount of physiological dorsovolar shift, so far, there is no reliable method of quantification of DRUJ mobility in daily practice. The aim was to describe a novel sonographic method of quantifying DRUJ instability and evaluate its reliability and validity. In this study, 40 healthy volunteers and 17 patients with complete rupture of the triangular fibrocartilage complex (TFCC) underwent sonographic quantification of the grade of instability of their DRUJ bilaterally. Dorsovolar ulnar head translation relative to the distal radius was quantified by means of ultrasonography performed in a transversal plane through the ulnar head and Lister tubercle. Measurements were done while actively pressing the volar surface of the hand onto a brick 30 degrees pronated, and after lifting the hand. A quotient Q of the radioulnar distance (distance between the dorsal radius surface and the ulnar head) between the unloaded and loaded wrist was calculated for differentiation of a normal and unstable DRUJ. The Q ratio of the 17 patients with unilateral TFCC lesion was significantly different between the pathologic side and the contralateral wrist (1.19 vs. 0.54, p < 0.001). There was no significant difference in the Q ratio in the 40 healthy volunteers between the right and left side or dominant and nondominant wrist. A Q ratio > 0.8 was found to be a reasonable cut-off for pathologic laxity of the DRUJ with a sensitivity of 88% and a specificity of 81%. A quotient Q > 0.8 determines instability of the DRUJ reliably. This was a level II diagnostic study.
Keywords: physiological laxity; instability; unstable distal radioulnar joint; triangular fibrocartilage complex lesions; ultrasound